Insight on electrical and thermal powers mix with a Gen2 PWR: Rankine cycle performances under low to high temperature grade cogeneration. (1st July 2020) - Nguyen, H.D.; Alpy, N.; Haubensack, D.; Barbier, D.
Abstract: Performances of a Rankine PCS exemplary of the Gen2 PWRs fleet, are mapped under heat cogeneration. In the considered scenarios, steam latent heat is provided in a 146–285 °C range and cogeneration load rates up to 20% of SGs power. THERMOFLEX commercial software and CYCLOP in-house code are applied to balance cycle performances with and without taking into account turbine thermodynamic irreversibilities that arise from part-load operation. Deviations between both approaches highlight that the original cycle designed for a 100% electrical duty, does not deserve to be revised for a low temperature cogeneration application. Instead, growing of part-load irreversibilities indicates optimization possibilities of its design for high temperature grade cogeneration. As such, the most stringent cogeneration case shows a cycle electrical efficiency drop of 2.7 points if one considers a constant cycle bottoming pressure. An exergetic analysis outlines that the turbine governing valve which controls steam admission, plays a key entropic role while degradation of turbine efficiency and impact of SG feed water temperature change, remain low. Shift of turbine expansion lines to lower pressures is the reason for a weakly changed turbine efficiency, by reducing stage losses contribution due to steam moisture content. Highlights: Performances of a cogenerating steam cycle, exemplary from Gen2 PWRs fleet, are calculated. Steam latent heat is provided in a 146–285 °C range and load is up to 20% of SGs power. Low temperature cogeneration does not deserve to revise cycle original design. Possibilities for cycle design optimization are outlined for high temperature cogeneration. Exergetic analysis identifies turbine governing valve as a main contributor to losses.